KEDISIPLINAN BELAJAR SISWA DALAM PROSES PEMBELAJARAN DI SEKOLAH DASAR - Siti Zunainah Maulidia; Agustinus Toding Bua; A. Wilda Indra Nanna (Universitas Borneo Tarakan, 2021)
The aims of this study is to reveal the types of disciplinary learning of students in elementary schools, and the factors that influence them. This research uses descriptive quantitative design. The subjects of this study were 26 students of class III A, while 24 students of class III B were used to trial questionnaire research instruments. The data collection technique was carried out through distributing questionnaires which were then followed up through an interview process. Based on the results of trials on 26 items of the learning discipline questionnaire, 24 items were declared valid and had very high reliability, namely 0, 979. The results showed that in the aspect of student attendance, both male students and female students were included in the very strong category. In the aspect of following lessons in class, female students are in the very strong category, while male students are in the strong category. In the aspect of doing assignments, both male, and female students are in the strong category, and in the aspect of external, and internal factors are also in the strong category.